Are Postcolonial Narratives useful in Al-Andalus Archaeology? - García-Contreras, Guillermo (ANDULI, Revista Andaluza de Ciencias Sociales, 2021)
Archaeological investigations of al-Andalus has become increasingly important in medieval studies, but it has traditionally been left out of the research agenda of European medieval archaeology. This is due to its exoticism and not fitting in well with the construction of a European identity and Spanish national history based on Christian expansion and the “Reconquest” process. At the same time, due to the geographical location and geopolitical position of the Iberian Peninsula within the “West”, scholars working on Islamic archaeology have dedicated less attention to al-Andalus than to other territories. Several factors pose a challenge for current research: the possibility of confrontation with feudal societies; the increasing importance given to technological transfer all along al-Andalus; religious, economic and institutional differences within Christian territories; the importance given in recent years to the identity construction of alterity; and the strong impact that the Andalusi period had on the creation of current landscapes, especially due to irrigated agriculture. This paper tries to reflect on and analyze the historiographical arginality of al-Andalus in both European medieval archaeology and Islamic archaeology. The aim is to understand how we have built an international narrative of the marginality of a territory that is theoretically outside Europe and outside the environment in which classical Islam developed, based mainly on literature produced in English on this matter. In short, this paper poses the question of whether ostcolonial theory is a valid category of analysis for al-Andalus.